Effects of walnut green hsuk on the quality, bacterial community diversity and in vitro rumen digestion characteristics of whole-plant corn silage - Abulaiti, Naibi; Wang, Fangxia; Yimamu, Aibibula (Frontiers in Veterinary Science, 2026)
This experiment aimed to investigate the effects of adding walnut green husk (WGH) on the quality of whole-plant corn silage, bacterial community diversity, and in vitro rumen fermentation characteristics. The silage was prepared using whole-plant corn (Qidan 828) at the milk-ripening stage and walnut green husk (WGH, Xinwen 185) as raw materials. Four treatments were established: CK (100% whole-plant corn), A1, A2, and A3, with WGH added at rates of 15, 30, and 45 g per kg of fresh matter, respectively. Each treatment was ensiled in laboratory-scale silos for 60 days under dark and anaerobic conditions at 16 °C−22 °C, with three replicates per group. The results indicated that WGH supplementation significantly elevated the DM and CP content and concurrently lowered the levels of acetic acid, propionic acid, and NH3-N (P < 0.05). Consequently, it increased the lactic acid bacteria population and reduced the yeast count (P < 0.05). This microbial shift ultimately led to improved aerobic stability. Compared to the CK group, adding WGH reduced the abundance and diversity of the microbial community. At the phylum level, significant shifts in microbial composition were observed. The relative abundance of Firmicutes_D was higher in the A2 and A3 groups than in the control. In contrast, the abundances of Bacteroidota, Proteobacteria, and unclassified bacteria were significantly reduced in these treatment groups. At the genus level, we observed an increase in the abundance of beneficial genera, including Lactiplantibacillus, Levilactobacillus, and Lacticaseibacillus. Thisenrichment of lactic acid bacteria significantly improved the overall bacterial community structure of the whole-plant corn silage. Among these, the A2 treatment had the highest relative abundance of dominant bacteria Firmicutes_D (82.79%), Lactiplantibacillus (66.48%), Levilactobacillus (14.03%), and Lacticaseibacillus (4.22%). During in vitro rumen fermentation, increasing the WGH ratio elevated the activity of all measured digestive enzymes except for protease. This enhancement further led to significant increases in IVDMD, IVCPD, and IVNDFD (P < 0.05). However, a significant decrease was observed in IVADFD (P < 0.05). This study confirms the feasibility of the functional utilization of WGH as an unconventional feed resource for enhancing silage quality by driving beneficial microbial shifts. Therefore, an inclusion rate of 30 g·kg−1 is recommended as the most appropriate to achieve optimal fermentation and digestibility. Future efforts should be directed toward practical application at scale and elucidating the modulatory mechanisms.